Effect of Coating Superparamagnetic Iron Oxide Nanoparticles with Oleic Acid and PEG on Their Properties For Magnetic Targeting Applications: A Review - Firyal Dhiya Khansa Arianna; Togar Saragi; Risdiana Risdiana (Department of Physics, Sebelas Maret University, 2025)
Superparamagnetic iron oxide nanoparticles (SPIONs) with all their unique properties have great potential in biomedical applications, including cancer treatment using targeted drug delivery systems and magnetic hyperthermia therapy. However, the stability of nanoparticles and their biocompatibility are major challenges in the success of these applications. Coating nanoparticles with oleic acid and polyethylene glycol (PEG) is often used to improve their dispersion stability and biocompatibility. In this review, we will discuss how the properties of SPION such as colloidal stability, magnetic properties, hyperthermia properties, drug loading, and drug release capabilities are improved when SPION is coated with oleic acid and PEG. It was found that in general, coating using oleic acid and PEG would improve the properties of SPION, such as increasing the hydrodynamic diameter and zeta potential values, and decreasing the polydispersity index and coercive filed values, making it more suitable for biomedical applications. This review aims to provide a thorough understanding of coating strategies to optimize SPION performance in magnetic targeting applications, and identify challenges and opportunities for future development